Reutilização da água na limpeza das instalações de suínos nas fases de crescimento e terminação - Silva, Mariana Fernandes Ribas da (2016)
This study had the purpose to test a system for reuse from the pig farming water. It evaluated the growth performance of animals subjected to cleaning the installations wastewater from swine, they were also evaluated the chemical quality, physical and biochemistry of wastewater and waste. The survey was conducted in the swine sector UFSM, we used 72 pigs, with initial and final weight of 18kg and 115kg respectively, distributed in two treatments (T1- cleaning the stalls with wastewater from swine; T2 pen cleaning with water from the artesian well) the phases of growing and finishing. Analysis of variance was performed and the results obtained, when significant, were submitted to the Student t test to compare means, using the SAS statistical program. Production indices were similar for both treatments (P> 0.05), demonstrating that the treatment system used did not affect the performance of the animals during the study period. The proposed waste treatment system met the objective of the work, because the wastewater obtained no influence on the performance of pigs. The main trace mineral supplements for pigs in growing and finishing Cu, Fe, Mn and Zn obtained a reduction in wastewater by 45%, 73%, 48% and 81% respectively in the growth phase. In the finishing phase Cu reduced 65%, Fe 72%, 70% Mn and Zn 30%. The DQO reduced 81% and 90% in the growing and finishing phases, respectively. The DBO got 38% reduction in the growth phase and 91% in the finishing phase. The pH values were similar between treatments in both phases.